2020
DOI: 10.3390/molecules25173872
|View full text |Cite
|
Sign up to set email alerts
|

Towards Higher Oil Yield and Quality of Essential Oil Extracted from Aquilaria malaccensis Wood via the Subcritical Technique

Abstract: A method that delivers a high yield and excellent quality of essential oil, which retains most of its value-added compounds, and undergoes least change after the extraction process, is greatly sought after. Although chemical free methods are acceptable, they call for an extensive processing time, while the yield and quality from these methods are often disappointing. This work utilizes subcritical water technology to address these issues. In this undertaking, essential oil was extracted from Aquilaria malaccen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…Grains, seeds, corn, and fruits have also been investigated using SBWE [ 21 ]. Among all papers reviewed, only one article reported that the wood of Aquilaria malaccensis has useful medicinal applications, and is used in traditional medicine to treat pain, fever, rheumatism, and asthma [ 22 ].…”
Section: Sample Matrices Extracted By Subcritical Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Grains, seeds, corn, and fruits have also been investigated using SBWE [ 21 ]. Among all papers reviewed, only one article reported that the wood of Aquilaria malaccensis has useful medicinal applications, and is used in traditional medicine to treat pain, fever, rheumatism, and asthma [ 22 ].…”
Section: Sample Matrices Extracted By Subcritical Watermentioning
confidence: 99%
“…Essential oils have been used in folk medicine in ancient China, Egypt, Arabia, and Greece throughout centuries. Therefore, some researches have attempted to utilize SBWE as a green solvent to extract essential oils from plants, and recent researches are illustrated in Table 6 [ 12 , 22 , 28 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 ]. The most common essential oils are extracted by distillation [ 174 , 176 , 180 , 181 ], n -hexane [ 174 ] or supercritical carbon dioxide [ 181 ], or dichloromethane [ 181 ].…”
Section: Compounds Extracted By Subcritical Watermentioning
confidence: 99%
“…Essential oils typically arise from secondary metabolites with several hundreds of constituents. However, oil quantity and quality in agarwood are reported to be markedly dependent on agarwood induction techniques [ 8 , 9 , 21 23 ]. There have been prior studies on the metabolite profiles of agarwood [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have indicated that both chromones and sesquiterpenes are essential for the medicinal and incense applications of agarwood [ 4 , 8 , 13 ]. Recently, it has been revealed that the quantity of chromones in agarwood fluctuates throughout agarwood production [ 25 ], but 2-(2-phenylethyl) chromones have been shown to accumulate significantly in high-quality agarwood [ 8 , 13 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation